2016
DOI: 10.1021/acs.jnatprod.5b01014
|View full text |Cite
|
Sign up to set email alerts
|

Biochemometrics for Natural Products Research: Comparison of Data Analysis Approaches and Application to Identification of Bioactive Compounds

Abstract: A central challenge of natural products research is assigning bioactive compounds from complex mixtures. The gold standard approach to address this challenge, bioassay-guided fractionation, is often biased towards abundant, rather than bioactive, mixture components. This study evaluated the combination of bioassay-guided fractionation with untargeted metabolite profiling to improve active component identification early in the fractionation process. Key to this methodology was statistical modeling of the integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
167
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(179 citation statements)
references
References 45 publications
3
167
0
Order By: Relevance
“…913 The improved access to DNA sequence information of prokaryotes has indicated that a staggering number of uncharacterized biosynthetic gene clusters are present in these organisms, and that there is much molecular diversity left to discover and explore for biologically valuable properties. 14 In turn, this has encouraged many researchers to pursue a “bottom-up” genetics-based discovery program.…”
mentioning
confidence: 99%
“…913 The improved access to DNA sequence information of prokaryotes has indicated that a staggering number of uncharacterized biosynthetic gene clusters are present in these organisms, and that there is much molecular diversity left to discover and explore for biologically valuable properties. 14 In turn, this has encouraged many researchers to pursue a “bottom-up” genetics-based discovery program.…”
mentioning
confidence: 99%
“…The traditional workflow for natural product discovery is bioassay-guided fractionation [12], in which bioactive extracts and subsequent fractions are chromatographically separated and retested for bioactivity until active compounds have been isolated. Because botanical extracts contain thousands of individual constituents, it is often difficult to assign activity to individual components, thus, the most abundant or easily isolatable compounds are often presumed to be responsible for bioactivity [34]. New methods are needed that will enable isolation efforts to be focused on those components most likely to be responsible for the desired biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with chromatographic techniques, mass spectrometry can be utilized to analyze hundreds of secondary metabolites simultaneously [3, 1516]. Using a process called biochemometrics, quantitative chemical information and biological activity data can be incorporated into a statistical model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations